2007
DOI: 10.1007/bf03026797
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Fatal hepatic failure after aortic valve replacement and sevoflurane exposure

Abstract: Purpose: To report a case of lethal hepatotoxicity possibly caused by sevoflurane. Clinical features:A 76-yr-old woman with a history of four previous minor surgical procedures developed acute liver failure after general anesthesia with sevoflurane, sufentanil and propofol for aortic valve replacement. After an uneventful procedure the patient was extubated 4.5 hr after surgery. On the second postoperative day, serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) increased. On the third po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…Hepatitis following anaesthesia induced by other inhalation anaesthetics has also been reported although it is rare [23][24][25]. …”
Section: Literature Reviewmentioning
confidence: 99%
“…Hepatitis following anaesthesia induced by other inhalation anaesthetics has also been reported although it is rare [23][24][25]. …”
Section: Literature Reviewmentioning
confidence: 99%
“…In the clinical studies, Kharasch (25) and Kharasch et al (26) reported no hepatotoxic effects of sevofl urane, the new volatile anaesthetics, and insignifi cant rates of hepatic dysfunction (25,27); nevertheless, the number of reported cases with hepatotoxicity associated with sevofl urane has increased in recent years (8)(9)(10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…It has a low blood solubility, which results in a rapid induction and faster recovery (7). Although there are reports of sevofl urane-associated liver injury in the literature (8)(9)(10)(11)(12)(13), sevofl urane is considered less hepatotoxic than the older inhalational agents (14).…”
mentioning
confidence: 99%
“…In der Studiengruppe zeigte sich ein geringerer postoperativer Anstieg der leberspezifischen Transaminasen (AST, ALT; [5]). Es liegt jedoch der Fallbericht eines fulminant verlaufenden Leberversagens nach Aortenklappenersatz vor, der in Zusammenhang mit einer Sevofluranexposition gebracht wurde [66]. Trotz dieser fatalen, einzelnen Komplikation ist aufgrund der Anwendung von Sevofluran in verschiedenen leberchirurgischen Zentren und bei zahlreichen herzchirurgischen Patienten von einem klinisch akzeptablen Sicherheitsprofil auszugehen.…”
Section: Totale Vaskuläre Okklusionunclassified